Corporate governance, risk management and financial performance of listed deposit money bank in Nigeria - Abiola Kafidipe (Taylor & Francis Group, 2021)
This study examined corporate governance, risk control in deposit money banks and how operational problems within commercial banks and information on them in Nigeria has been hoarded to a great extent. The result shows a negative but a significant impact on bank's financial performance. However, a corporate-governance system that is sound increases the profitability of loans as well as the stability of banks. Furthermore, the study finds that board size, board independence, directors’ shareholdings and board meetings are negative while the coefficient number of board committee is positive on Tobin Q. It, therefore, means that there exists between the corporate governance a significant relationship with financial performance. Shareholders, board meetings & members of the board does have negative relationship to performance. In contrast, the coefficient for the number of board sizes, board independence & board committees are positive on ROE-Return on Equity. This shows that any increase in shareholding of directors, the directors of the board and board of directors would result in decreased ROE of deposit money banks (DMB) in the economy of Nigeria. This research then recommends proper corporate risk management practices should be encouraged with financial institutions carrying out frequent quality control checks to ensure compliance.